Laboratory Measurement of the Brighter-fatter Effect in an H2RG Infrared Detector. (25th April 2018) - Plazas, A. A.; Shapiro, C.; Smith, R.; Huff, E.; Rhodes, J.
Abstract: The "brighter-fatter" (BF) effect is a phenomenon—originally discovered in charge coupled devices—in which the size of the detector point-spread function (PSF) increases with brightness. We present, for the first time, laboratory measurements demonstrating the existence of the effect in a Hawaii-2RG HgCdTe near-infrared (NIR) detector. We use JPL's Precision Projector Laboratory, a facility for emulating astronomical observations with UV/VIS/NIR detectors, to project about 17, 000 point sources onto the detector to stimulate the effect. After calibrating the detector for nonlinearity with flat-fields, we find evidence that charge is nonlinearly shifted from bright pixels to neighboring pixels during exposures of point sources, consistent with the existence of a BF-type effect. NASAs Wide Field Infrared Survey Telescope ( WFIRST ) will use similar detectors to measure weak gravitational lensing from the shapes of hundreds of million of galaxies in the NIR. The WFIRST PSF size must be calibrated to ≈0.1% to avoid biased inferences of dark matter and dark energy parameters; therefore further study and calibration of the BF effect in realistic images will be crucial.